Fluoride and Titanium Based Orthodontic Arch wire (Review article) - Haidar M. AL Sharifi, / Akram F. Alhuwaizi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
Fluoride is commonly employed in toothpaste and mouthwashes in concentrations of up to 1%, whereas for the purpose of addressing enamel discolorations, concentrations of approximately 2% are utilized.  The potential of dental hygiene products containing fluoride ions to degrade the oxide deposit generated on titanium surfaces raises concerns regarding the suitability of titanium for dental applications. When conducting a search on PubMed using the keywords "fluoride" and "titanium orthodontic wires," a total of approximately 105 results were obtained. The bulk of these studies primarily focus on investigating the impact of fluoride on various mechanical characteristics of orthodontic wires (like friction, surface roughness, load deflection). for that this review focus on effect of fluoride on friction and surface roughness of titanium-based wire and it found that fluoride significantly affect.